PEDT-5 Problem for the guideline of CNS germ cell tumors. (6th December 2021) - Nakamura, Hideo; Yanagisawa, Takaaki; Soejima, Toshinori; Yokoo, Hideaki; Nishikawa, Ryo; Fujimaki, Takamitsu; Hara, Junichi; Terashima, Keita; Sonoda, Yukihiko; Arakawa, Yoshiki; Kumabe, Toshihiro; Sugiyama, Kazuhiko; et al.
Abstract: Primary CNS germ cell tumors (GCTs) are rare neoplasms, therefore, a clinical guideline has not been established so far. While better management has been achieved over recent decades by modifying radiation coverage and selecting appropriate chemotherapy, standardization of treatment remains challenging, partly due to the low volume of cases encountered in each institution. As the incidence is higher in East Asia, including Japan, the Japan Society for Neuro-Oncology established a multidisciplinary task force to create an evidence-based guideline for CNS GCTs. The Medical Information Network Distribution Service (Minds) guideline was referred to and utilized in the course of creating this guideline. We chose 6 topics and 10 clinical questions. This guideline provides recommendations for multiple dimensions of clinical management for CNS GCTs, with particular focus on diagnostic measures including serum markers, treatment algorithms including surgery, radiotherapy and chemotherapy, and under-investigated but important areas such as treatment for recurrent cases, long-term follow-up protocols and long-term sequelae. International collaborations to set standards of clinical management for this rare tumor have proven fruitful, concurrently, many fields continue to show variance in clinical practice, partly due to the rarity of clinical encounters and the absence of documented standards. There still seem to be differences in the treatment concept between Japan and North America or Europe countries. This guideline serves the purpose of helping healthcare professionals keep up to date with current knowledge and standards of management for patients with this rare disease in daily clinical practice, as well as driving future translational and clinical research by recognizing unmet needs concerning this tumor. We discuss about the issues both already clarified and should be cleared in the future.